An Investigation on Acoustic Wave Focalization by a Square Lattice Flat Lens - ALAGOZ, Serkan (Archives of Acoustics, 2012)
A sonic crystal consists of a finite-size periodic array of scatters embedded in a background material.One of the fascinating properties of sonic crystals is the focusing phenomenon. In this study, the nearfield focusing effect of a solid-air 2D sonic crystal lens with a square lattice configuration is investigatedin the second frequency band. The band structure and equifrequency contour of the crystal are analyzedto reveal the dispersion of an acoustic wave on the crystal structure. The frequency dependence of theacoustic wave focalization by the sonic crystal flat lens is demonstrated via Finite Difference Time Domainsimulation results and experimental measurements.